2019
DOI: 10.1097/ncm.0000000000000318
|View full text |Cite
|
Sign up to set email alerts
|

Improving Early Discharge Using a Team-Based Structure for Discharge Multidisciplinary Rounds

Abstract: Purpose of Study: Miscommunications during the complex process of discharging patients from acute care facilities can lead to adverse events, patient dissatisfaction, and delays in discharge. Brief multidisciplinary discharge rounds (MDRs) can increase communication between stakeholders and shorten a patient's length of stay (LOS). At our tertiary academic medical center, case managers (CMs) have historically been assigned patients by physical unit location rather than by provider teams caring for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
37
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 15 publications
3
37
0
2
Order By: Relevance
“…In this study, our intervention was associated with a significant increase in DCBN comparing the preintervention to the postintervention periods. Previous studies have shown that increased DCBN through quality improvement efforts is an achievable goal 2,3,5,8 . Many of these initiatives have been conducted in medicine units, and this study represents one of the few studies specific to a surgical service.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, our intervention was associated with a significant increase in DCBN comparing the preintervention to the postintervention periods. Previous studies have shown that increased DCBN through quality improvement efforts is an achievable goal 2,3,5,8 . Many of these initiatives have been conducted in medicine units, and this study represents one of the few studies specific to a surgical service.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that increased DCBN through quality improvement efforts is an achievable goal. 2,3,5,8 Many of these initiatives have been conducted in medicine units, and this study represents one of the few studies specific to a surgical service. We were able to increase our DCBN percentage from 8% to above 50%, reaching the goal for the first time in September 2016.…”
Section: Discussionmentioning
confidence: 99%
“…Communication across care teams and improved interdisciplinary care has been recognized as an important factor for high-quality patient-centered care and for high-functioning teams. Studies have shown that when care teams communicate better, efficiency outcomes are improved [ 18 ]. Patients have also expressed a need for the clinical staff caring for them to communicate with each other more effectively [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…14 Numerous specific interventions to manage capacity strain and optimize patient flow have been described in the literature, including strategies that focus on earlier discharges, huddles, and reducing unnecessary hospital days. [17][18][19][20][21] It is clear that hospital flow is of strategic importance to many hospital systems; however, the perceived impact of the various strategies has not been well studied.…”
Section: Introductionmentioning
confidence: 99%